Credit Market Liberalization Reform Outcomes - Zukhba, D.S.; Shpynova, K.V. (Економічний вісник Донбасу, 2013)
This article deals with the process of credit market liberalisation in different countries and the main tools for conducting the reform. The impact of financial liberalisation on economic growth in the most developed countries has been determined. The article represents the basic indicators of economic development in countries with the most developed credit markets.